At the intersection of markets: EFTA investments in the area of Hamburg/Schlesivig-Holstein - Ingeborg Zaunitzer-Haase (Intereconomics, 1966)
About a year ago Herr Kurt Ladendorff, auditor in Hamburg, caused quite a sensation with his projected establishment of “europoint”, an international conference centre in the Hamburg suburb of Wedel, located in Schleswig-Holstein. Whilst the interest of local papers concentrated on the projected super-hotel, the restaurants for gourmets, bowling-alleys, and other recreation centres, the interest of experts focussed on the question of why it should be the Hamburg region where such an international meeting centre is to be established. According to the wishes of its planner “europoint” is to be an international meeting centre not only between the economic blocs—i.e. above all between EEC and EFTA — but over and above this a show-window, a permanent trade fair for EFTA firms establishing themselves in the Common Market. Particularly in view of this latter task no better location could be thought of. Last years' company promotions in the EEC area, initiated by firms domiciled in EFTA countries, have been concentrating conspicuously on the Hamburg/Schleswig-Holstein region. In the following contribution our author investigates kind, size, and importance of these company promotions.
Keywords: 330